Former Yugoslav Republic of Macedonia : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2001 Article IV Consultation highlights that after three consecutive years of generally favorable performance, the economy of the Former Yugoslav Republic of Macedonia (FYRM) suffered a setback in 2001 because of a six-month security crisis. Output declined markedly and new outlays on security operations and weak revenues contributed to a large expansionary fiscal swing. Owing to a deterioration of the external current account position, the foreign exchange loss was heavy. However, the impact on reserves was cushioned by sizable privatization inflows in early 2001.